Picture Freedom : Remaking Black Visuality in the Early Nineteenth Century - Cobb, Jasmine Nichole (Book collections on Project MUSE., 2016)
In the decades leading up to the end of U.S. slavery, many free blacks sat for daguerreotypes decorated in fine garments to document their self-possession. People pictured in these early photographs used portraiture to seize control over representation of the free black body and reimagine black visuality divorced from the cultural logics of slavery. In 'Picture Freedom', Jasmine Nichole Cobb analyzes the ways in which the circulation of various images prepared free blacks and free whites for the emancipation of formerly unfree people of African descent.